2017
DOI: 10.3892/ijo.2017.4137
|View full text |Cite
|
Sign up to set email alerts
|

The receptor for activated protein kinase C promotes cell growth, invasion and migration in cervical cancer

Abstract: Cervical cancer is one of the most common malignant tumors in women all over the world. However, the exact etiology of cervical cancer remains unclear. The receptor for activated protein kinase C (RACK1) is reported to be involved in tumorigenesis and tumor progression. Besides, the prognostic value of RACK1 in several kinds of tumors has been identified. However, there are limited studies on the functional role of RACK1 in cervical cancer. In this study, we tested the expression level of RACK1 by immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…31,32 For the CCK8 assay, 1 × 10 4 cells were grown in 96-well plates in which CCK-8 reagent was added according to the standard protocol (Beyotime, Beijing, China). 31,32 For the CCK8 assay, 1 × 10 4 cells were grown in 96-well plates in which CCK-8 reagent was added according to the standard protocol (Beyotime, Beijing, China).…”
Section: Cell Proliferation Migration and Invasion Assaysmentioning
confidence: 99%
“…31,32 For the CCK8 assay, 1 × 10 4 cells were grown in 96-well plates in which CCK-8 reagent was added according to the standard protocol (Beyotime, Beijing, China). 31,32 For the CCK8 assay, 1 × 10 4 cells were grown in 96-well plates in which CCK-8 reagent was added according to the standard protocol (Beyotime, Beijing, China).…”
Section: Cell Proliferation Migration and Invasion Assaysmentioning
confidence: 99%
“… 10 , 11 Worldwide, a large number of new cervical cancer cases are diagnosed every year, and more than half of patients diagnosed died from the cancer. 3 Tumor progression involves tumor cell proliferation and metastasis and novel targeted therapeutic strategies are urgently required for patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the second most common malignancy in women with an estimated 530,000 new cases and 275,000 deaths annually worldwide, 1 , 2 and the majority of female cancer deaths occur in developing countries. 3 Various treatments for cervical cancer are available, according to tumor grade and stage, including surgery and radiation therapy. However, treatment for advanced stage cervical cancer remains a public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a favorable prognosis and increased long-term survival time are correlated with early CC diagnosis and appropriate therapy [15]. Several studies have demonstrated that abnormal molecular biology can predict the prognosis of tumor patients [16][17]. However, in these studies, no single bio-maker that was used to detect CC was both highly sensitive and specific.…”
Section: Discussionmentioning
confidence: 99%
“…Higher GNB2L1 expression was associated with an advanced FIGO stage, lymph node metastasis, and the degree of cell differentiation. GNB2L1 is reported to be upregulated in multiple cancers including oral squamous carcinoma [19], hepatocellular carcinoma [20], and pancreatic ductal adenocarcinoma [11]. A previous study by Liao and colleagues indicated that overexpression of GNB2L1 promotes CC cell proliferation and invasion by affecting the p53 signaling pathway [21].…”
Section: Discussionmentioning
confidence: 99%